China and the Indo-Pacific : issues and concern - Singh, Teshu (New Delhi : Indian Council of World Affairs, 2023)
There has been a shift in the geopolitics; the new concept of the "Indo-Pacific" has entered the geopolitical discourse by replacing the term, Asia Pacific. The Indo-Pacific refers to a contiguous zone encompassing the Pacific and Indian Oceans. The geographical boundaries of the Indo-Pacific stretch from East Africa to the west coast of the US and encompass a large number of countries at varying stages of development, with distinct policy agendas and divergent interests. In June 2018, Prime Minister Narendra Modi presented India's vision of "Indo-Pacific" in his keynote address at the Shangri-La Dialogue. He described "Indo-Pacific" as a natural region, and concretely as a region "from the shores of Africa to that of the Americas". However, each country has its definition about the stretch of the concept. In recent times, the concept of Indo-Pacific has evolved and has become the primary space for the geostrategic contestations. The paper investigates into the Chinese position on the concept and its responses to the evolving frameworks in the Indo-Pacific region. It brings out four levels of analysis of the Chinese Ministry of Foreign Affairs, Think Tanks, University and the media coverage on the Indo-Pacific region within China. It further makes an attempt to decipher the Chinese postures in the region by analysing the China's Defence White Papers and attempts to comprehend the overall Chinese objectives in the Indo-Pacific region.
English.
Keywords: Indo-Pacific Region -- Politics and government; China $1 (BForeign relationss -- Indo-Pacific Region; Geopolitics -- Indo-Pacific strategy; International relations -- Strategic aspects -- Indo-Pacific Region; China $1 (BMilitary policys -- Strategic aspects -- Indo-Pacific Region